Implementing Authentic Reading Material to Improve Reading Comprehension Skill of The Tenth Grade Students at SMK 17 Agutus 1945 Muncar Banyuwangi - Ridwan, Ridwan (IAI Darussalam, 2019)
This study aims to improve students’ reading skills through authentic reading material. Classroom action research (CAR) aims to discover teaching and learning strategies that match the style of the learner and to overcome teacher problems in getting the right techniques in teaching. Research hold in SMK 17 August 1945 Muncar Banyuwangi on 27 students of class X APH1 done in two cycles with stages of planning, implementing, observing, and reflecting. Instruments used for data collection are observation sheets, questionnaires and student opinions about the authentic reading material. The teaching and learning procedure is cleaved into three steps; pre-activity, main activity, and post-activity. A researcher found that the application of authentic reading material can improve the student’s reading skills.